Infrastructure as a key factor in the comprehensive training of students in the professional careers of Industrial Engineering, Food Industry Engineering and Agroindustrial Engineering of the Private University of Tacna - Torres Torres, Yanira Tatiana (2014)
Objective: Propose and develop the Architectural Design of Infrastructure Engineering Professional Racing as a solution to the lack of proper educational infrastructure that allows for comprehensive training become a key factor in the accreditation process. Methodology: The Descripitivo type was applied because no situation is not built, but we observe existing situations, not intentionally provoked by the researcher. Also use experimental research to validate that adequate educational infrastructure is a key determinant in shaping quality of engineering students. Results: The University quality is closely linked to the quality of their spatial configuration. This statement, empirically supported by centuries of architectural excellence in the Institutions of Higher Education, is but a conceptual elongation of a deeper reality: Learn the qualified transmission in any of its sociocultural and historical meanings, always has been accompanied an ad hoc spatial framework to promote and reinforce the ideology of the corresponding teaching model. Conclusion: The projection of an educational infrastructure for engineering students will bring considerable improvements in the educational experience and the development of necessary capacities to face the demands of globalized world. In this context, it is necessary to focus the efforts of the university community to training that also includes appropriate scenarios to develop the skills of students in Eng. Industrial, Eng. Food Industry and Eng. Agribusiness.